Corresponsabilidad de peatones y conductores en accidentes de tránsito en la provincia de Imbabura en el año 2022 - Arias Montalvo, Anthony Francisco (2024)
The shared responsibility between pedestrians and drivers in traffic accidents in the province of Imbabura should be conceived as a holistic social system, where different actors participate in various processes related to the use of transportation, whether motorized or non-motorized. The idea is proposed that this social system should ideally operate without conflicts or contradictions, with the primary goal of preserving human life and ensuring the optimal maintenance of road infrastructure. The objective of this study was to conduct a legal analysis to determine whether it is imperative to modify the regulations or create a culture of respect for road safety. The qualitative method was employed, applying research methods at both the theoretical and empirical levels to collect and analyze information about the current state of the study subject. The results from the unstructured interviews with key informants revealed that a legal modification alone would not be sufficient to change the attitude of pedestrians and drivers toward road-sharing responsibility. There is a highlighted urgent need to establish a comprehensive and effective road safety education. This education should not only impart practical knowledge but also foster a profound understanding of the relevance of shared responsibility in road safety.